Strategi Guru PAI Dalam Mengintegrasikan Nilai Abstrak Pada Kurikulum Merdeka Di MTS Ittihaadul Ulum Lubuk Linggau - Johan Effendi; Salsabila; Sefrida; Deri Wanto; Muhammad Idris; Epa Kristina (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2026)
This study aims to analyze the strategies of Islamic Religious Education (PAI) teachers in integrating abstract values within the Merdeka Curriculum at MTs Ittihaadul Ulum Lubuklinggau. Abstract values such as sincerity, patience, trust in God, responsibility, and gratitude are essential in shaping students’ character but are often difficult to understand when delivered only theoretically. This research employs a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation, and analyzed using qualitative data analysis techniques. The findings reveal that teachers implement several strategies, including project-based learning, differentiated instruction, interdisciplinary integration, digital technology utilization, and student reflection. Project-based activities such as social service and environmental projects effectively help students internalize abstract values through real-life experiences. However, challenges remain, particularly students’ difficulty in understanding abstract concepts and limited digital facilities. These challenges are addressed through contextual teaching approaches and creative use of simple learning media. The study implies that integrating abstract values into PAI learning strengthens students’ Islamic character and enhances the relevance of education in the modern era. These strategies can be adopted and further developed in other Islamic educational institutions.